« Ilé Tuntun » à La Havane - Alain Konen (Ateliers d'Anthropologie)
This paper offers a detailed ethnography of a shrine house based in Havana called Ilé Tuntun, whose leader is the babalawo (priest-diviner of Ifá) Frank Obeché. Ilé Tuntun aims, with the help of Yoruba political and religious dignitaries, to re-establish lost links with Africa and reform Ifá’s practice in Cuba. Ilé Tuntun embodies a current tendency among various Cuban babalawos, who are interested in developing contacts with Yoruba. But this group also offers a very specific discourse as well as significant ritual innovations that aim to unite Cuban babalawos. The claim of a new ritual filiation (or African ancestry) as well as an innovative and learned discourse—based, in particular, on elements stemming from exchanges with Nigerian dignitaries who visited Cuba—are the key-elements that sustain the project. This paper analyses this discourse and its ritual implications, drawing on data collected during a field study with the group. In some ways, these efforts of Ilé Tuntun show continuity with similar attempts that have been made in the past, but they also exemplify more contemporary changes in the Cuban ritual field. However, judging by the reactions of numerous babalawos based in Havana, they appear to be controversial for two reasons. First, Ilé Tuntun, by renewing and reinterpreting historical links to Africa, advocates a ritual subordination to Yoruba religious and political dignitaries. In this sense, the group challenges the legitimacy of Cuban babalawos legitimacy. Secondly, Ilé Tuntun claims supremacy, and its leader claims supremacy and authority, over the babalawo community. The very idea of a possible Ifá unification arouses distrust among Cuban babalawo, and Frank Obeché’s claims of possessing Yoruba royal titles is also doubted by many of his peers, who keep their distance from him and from the group. Still, controversial though it may be, Ilé Tuntun has real visibility in the Cuban capital.